Understanding the thinking classroom - Presseisen, Barbara; Presseisen, Barbara (Arlington Heights, IL : SkyLight Training and Publishing, 1999)
Interview with Barbara Presseisen, former professor at Temple University and Swarthmore College who describes effective practices for impacting student thinking skills
Excutive producer, Ela Aktay
Keywords: Creative thinking in children; Children with social disabilities -- Education -- United States; Critical thinking -- Study and teaching -- United States; Critical thinking -- Study and teaching (Higher) -- United States